Efektivitas Media Tanam Untuk Perbanyakan Spora Glomus Hasil Isolasi dari Rizosfer Pternandra echinata Jack. - Dezi Meutya Dapersal; - Suwirmen; Zozy Aneloi Noli (Universitas Andalas, 2014)
The study about effectivity of growth medium for multiplication Glomus spores isolated from the rhizosphere Pternandra echinata Jack. has been conducted from February to November 2013 in the greenhouse and Plant Physiology Research Laboratory Department of Biology, Faculty of Mathematic and Natural Science Andalas University. The aims of the study to determine the appropriate type of media for multiplication Glomus isolated from rhizosphere Ptenandra echinata. The study used a Completely Randomized Design with 3 treatments and 9 replications. The treatment consists of the type of media used are sand, zeolite, and zeolite sand. The results showed that statistically media used gives a significantly different effect on the increase in plant height and number of leaves. Meanwhile the spore density and dry weight of the spores will show results that are not significantly different. Percentage of degree infection maize in all growth medium showed high criteria. Generally, the growth medium sand, zeolite, zeolite sand effective for spore multiplication glomus isolated from Pternandra echinata Jack.Keywords : Effectivity, Glomus, Growth Medium